Towards Remembering The Sufi Philosophy: Deconstruction of Boundary Oppositions in Doris Lessing's Briefing for A Descent Into Hell - Gündoğdu, Burcu (My University, 2016)
The aim of this article is to investigate how in her novel, Briefing for a Descent into Hell, Doris Lessing deconstructs binary oppositions. In the novel, it is argued that the previous descenders of God are sent to earth to spread the Sufi motto, “Life is one”, but the humankind forget the given knowledge in the course of life. Failing to perform God’s message, the society begin to act as individuals and create social boundaries gradually. In Lessing’s novel, the main character, Charles Watkins, descents into madness and retrieves the Sufi Knowledge as the previous messengers did. His descend into madness enables him to explore the blind spots in ideologies and their impacts on his identity. Although Watkins has to return to his old habits and social life through electric shock in the ending, it can be argued that Watkins acknowledges the importance of both the ordinary truth and the inner truth through his experience of Platonic immanence and transcendence simultaneously. Together with this, the letters sent to Watkins would enable the readers to see and question the inner workings of ideological indoctrination of war, language, science and education. In this article, utilizing from Platonic, Jungian, Irigarian and Derrida’s similar theories on boundary oppositions, it will be argued that Watkins undermines Plato’s hierarchical dualism between phenomenal and material world so as to realize “transcendent function” in Jungian sense and recalls the forgotten Sufi doctrine called “oneness”.

Bu makalenin amacı, Doris Lessing’in romanı, Cehenneme İniş için Açıklama ’da ikili karşıtlıkları nasıl yıktığını araştırmaktır. Romanda, tanrının Sufi sloganı olan, “Hayat Birdir”, öğretisini yaymak için insanları önceden dünyaya gönderdiği, fakat insanların yaşam döngüsü içinde verilen bilgiyi unuttuğu tartışılmaktadır. Tanrının mesajını yerine getirmeyen insanlık, zaman içinde birey olarak hareket etmeye ve ikililik oluşturmaya başlamaktadır. Lessing’in romanında, Charles Watkins delirir ve tanrının diğer peygamberleri gibi Sufi öğretisine erişir. Delirmesi, Watkins’in ideolojilerdeki kör noktaları ve bunların insanların kimliğindeki etkisini keşfetme fırsatına sahip olmasını sağlar. Her ne kadar romanın sonunda, elektrik şoku verilmesiyle eski alışkanlıklarına ve sosyal yaşamına geri dönse de, Watkins’in zihinsel yolculuğu, onun Plato’un dünyevi ve fenomenal dünyasını aynı anda tecrübe etmesini, böylece hem sıradan ve hem de içsel gerçeğin önemini anlamasını sağlayarak iç görü kazanmasını sağlamıştır. Bununla birlikte, Watkins’e gönderilen mektuplar, okuyucunun, beyin yıkayan; savaş, dil, bilim ve eğitim gibi ideolojik kavramların altında yatanları görmesini ve sorgulamasını sağlar. Bu makalede, Plato, Jung, Irigiray ve Derrida’nın ikili karşıtlıklar üzerine olan teorilerini ele alarak, Watkins’in Plato’a ait kuramda geçen fenomenal ve dünyevi arasındaki hiyerarşik ikiciliği yıkarak Jung’a ait “transendant fuction’ ını” gerçekleştirmesi ve unutulmuş olan,“ birlik/ bütünlük ”anlamındaki sufi öğretisini hatırlamayı amaçladığı tartışılmaktadır.
Sufi Öğretisinin Hatırlama Yolunda: Doris Lessing'in Cehenneme İniş İçin Brifing Romanında İkili Karşıtların Yıkımı
Keywords: Doris Lessing; Charles Watkins; Boundary Oppositions; Sufi Philosophy; Doris Lessing; Charles Watkins; İkili Karşıtlıklar; Sufi Öğretisi; Doris Lessing; Charles Watkins; İkili Karşıtlıklar; Sufi Öğretisi